Aktivitas Ekstrak Etanol Kulit Batang Kayu Jawa (Lannea coromandelica) terhadap Penyembuhan Luka Sayat pada Tikus Putih (Rattus Norvegicus L.): Activity of Ethanolic Extract of Jawa Bark (Lannea coromandelica) on Healing Wound at White Rat (Rattus Norvegicus L.) - Calsum, Umi; Khumaidi, Akhmad; Khaerati, Khildah (Universitas Tadulako, 2018)
Jawa bark (Lannea coromandelica) is a part of the plant that can be used empirically for handling wounds. This study aims to determine the activity of ethanol extract of Jawa bark on healing wound and determine the effective dose compared with povidone iodine. The test animals used were white rats (Rattus norvegicus L.) consisting of 5 groups, namely negative control (vaseline without extract), positive control (povidone iodine), dose of 250 mg/kg BW, dose of 500 mg/kg BW, dose of 750 mg/kg BW. Each rat made an incision in the area parallel to the spine with 2 cm long and 2 mm deep. Measuring the length of the wound was done every day for 14 days. The data obtained were analyzed statistically using One Way Anova and followed by Post Hoc Duncan test. Statistical results showed that the ethanol extract of Jawa bark has an activity in curing slice where the effective dose is a dose of 500 mg/kg BW with a wound healing time of 12 days.